2010
DOI: 10.5120/125-241
|View full text |Cite
|
Sign up to set email alerts
|

Email classification for Spam Detection using Word Stemming

Abstract: Unsolicited emails, known as spam, are one of the fast growing and costly problems associated with the Internet today. Among the many proposed solutions, a technique using Bayesian filtering is considered as the most effective weapon against spam. Bayesian filtering works by evaluating the probability of different words appearing in legitimate and spam mails and then classifying them based on that probabilities.Most of the current spam email detection systems use keywords to detect spam emails.These keywords c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The authors used J48 algorithm in order to formulate rules to generate concepts of the ontology. The study by Renuka and Hamsapriya [15] adapted the use of word stemming instead of simply content based words for spam email detection. The authors showed that stemming based method is more efficient as compared to content based methods.…”
Section: Spam Email Detectionmentioning
confidence: 99%
“…The authors used J48 algorithm in order to formulate rules to generate concepts of the ontology. The study by Renuka and Hamsapriya [15] adapted the use of word stemming instead of simply content based words for spam email detection. The authors showed that stemming based method is more efficient as compared to content based methods.…”
Section: Spam Email Detectionmentioning
confidence: 99%
“…Hasil dari penelitian sebelumya yang dilakukan oleh Renuka & Hamsapriya [1] menggunakan pengaplikasian word stemming akurasi dari metode Naïve Bayesian dapat ditingkatkan sampai 5-10% dimana metode naïve bayes lebih baik daripada metode random forest. Sedangkan penelitian menggunakan metode random forest yang dilakukan oleh Akinyelu & Adewumi [2] mendapatkan nilai presisi yang cukup tinggi dibanding metode naïve bayes dan tingkat kesalahan yang rendah.…”
Section: Pendahuluanunclassified
“…Rusland et al [5] worked on enhancing the conventional spam detection technique which uses Naïve Bayes algorithm for classification of spam mails. Renuka and Hamsapriya [9] analysed spam filtration. Bayesian filter works by testing the probability of various words appearing in legitimate, valid and spam mails and then classifying them based on those probabilities as spam or not [9].…”
Section: Related Workmentioning
confidence: 99%
“…Renuka and Hamsapriya [9] analysed spam filtration. Bayesian filter works by testing the probability of various words appearing in legitimate, valid and spam mails and then classifying them based on those probabilities as spam or not [9]. Shabbir and Mithun [3] showed that if some sort of word stemming or word hashing technique is used that can extract the base or stem of a misspelled or modified word, then the efficiency of any content based spam filter can be significantly improved [10].…”
Section: Related Workmentioning
confidence: 99%